2022
DOI: 10.3389/fphar.2022.997188
|View full text |Cite
|
Sign up to set email alerts
|

Antiarrhythmic calcium channel blocker verapamil inhibits trek currents in sympathetic neurons

Abstract: Background and Purpose: Verapamil, a drug widely used in certain cardiac pathologies, exert its therapeutic effect mainly through the blockade of cardiac L-type calcium channels. However, we also know that both voltage-dependent and certain potassium channels are blocked by verapamil. Because sympathetic neurons of the superior cervical ganglion (SCG) are known to express a good variety of potassium currents, and to finely tune cardiac activity, we speculated that the effect of verapamil on these SCG potassium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…AF is the most common cardiac arrhythmia and results from shortening of atrial effective refractory periods and from a localized deceleration of intra-atrial conduction ( 76 78 ). In this context, we recently have shown that verapamil (a class IV antiarrhythmic drug used in pathological conditions such as chronic angina pectoris, cardiac arrhythmias or hypertension) reduces the TREK-1 activity ( 79 ). TREK-1 channels may have a role in other pathophysiological situations, during ischemia, when purinergic agonists such as ATP cause the release of arachidonic acid (AA) ( 80 ), which lowers intracellular pH, the change of pH/AA can be detected by TREK-1 ( 63 ) and could contribute to electrophysiological disturbances in the cardiac mechano-electric feedback ( 81 ).…”
Section: Role Of Trek Channels In the Cardiovascular Systemmentioning
confidence: 99%
“…AF is the most common cardiac arrhythmia and results from shortening of atrial effective refractory periods and from a localized deceleration of intra-atrial conduction ( 76 78 ). In this context, we recently have shown that verapamil (a class IV antiarrhythmic drug used in pathological conditions such as chronic angina pectoris, cardiac arrhythmias or hypertension) reduces the TREK-1 activity ( 79 ). TREK-1 channels may have a role in other pathophysiological situations, during ischemia, when purinergic agonists such as ATP cause the release of arachidonic acid (AA) ( 80 ), which lowers intracellular pH, the change of pH/AA can be detected by TREK-1 ( 63 ) and could contribute to electrophysiological disturbances in the cardiac mechano-electric feedback ( 81 ).…”
Section: Role Of Trek Channels In the Cardiovascular Systemmentioning
confidence: 99%